Study on Optimization of Extrusion Process for Polypropylene/Ultra High Molecular Weight Polyethylene as Fused Filament Fabrication (FFF) 3D Printer Material - Christopher, Shahrul Izwani; Khairu Kamarudin; Fakrul Nur Aiman; Mohd Khairuddin M.S; Siti Nur Hanifah Zamri (Progress in Engineering Application and Technology, 2026)
This study focused on the development and optimization of polypropylene (PP) and ultra-high molecular weight polyethylene (UHMWPE) composite filaments for fused filament fabrication (FFF) 3D printing. An 80:20 PP/UHMWPE blend was selected to enhance mechanical performance while maintaining printability. Filament extrusion parameters were optimized using a design of experiments (DOE) approach, identifying an optimal temperature of 180 °C and extrusion speed of 110 mm/s. The optimized filament exhibited good dimensional stability with an average diameter of 2.78 mm. Mechanical testing showed that the PP/UHMWPE composite achieved a 19.3% increase in ultimate tensile strength compared to pure PP, along with improvements in stiffness and toughness. These results demonstrate the strong potential of PP/UHMWPE composite filaments for FFF applications requiring improved strength and reliability.